SOFTWARE FOR PROCESSING OF DIGITIZED ASTRONEGATIVES FROM ARCHIVES AND DATABASES OF VIRTUAL OBSERVATORY - Protsyuk, Yu. I.; Kazantseva, L. V.; Andruk, V. N. (Одеські астрономічні публікації, 2014)
The paper discusses and illustrates the steps of basic processing of digitized image of astro negatives. Software for obtaining of a rectangular coordinates and photometric values of objects on photographic plates was created in the environment LINUX / MIDAS / ROMAFOT. The program can automatically process the specified number of files in FITS format with sizes up to 20000 x 20000 pixels. Other programs were made in FORTRAN and PASCAL with the ability to work in an environment of LINUX or WINDOWS. They were used for: identification of stars, separation and exclusion of diffraction satellites and double and triple exposures, elimination of image defects, reduction to the equatorial coordinates and magnitudes of a reference catalogs